Dinamika Kepercayaan Diri pada Calon Siswa Kepolisian dalam Menghadapi Seleksi Penerimaan Polri - Hanifah Arien Faradilla; Ummi Nabila Azaria; Aldila Dyas Nurfitri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The recruitment process for Indonesian National Police (Polri) candidates requires physical, academic, and psychological readiness, including self-confidence. This study aims to explore the dynamics of self-confidence among police candidate students in facing the Polri selection process. A qualitative approach with a case study design was employed. The participant was a police candidate who had participated in the selection process twice. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that the participant’s self-confidence developed dynamically through preparation, competition, failure experiences, and social support. Careful preparation served as the primary source of confidence, while competitive pressure generated doubt that encouraged further self-improvement. Failure was not interpreted as a setback but as a means of reflection and self-enhancement. In addition, family and environmental support played a crucial role in maintaining motivation and confidence. The study concludes that self-confidence among police candidates is shaped by the interaction between personal experience, social support, and meaning-making processes in facing challenges. These findings highlight the importance of psychological strengthening in Polri selection preparation.